The Role of K.H. Muhammad Tahir (Imam Lapeo) in Integrating Sufi Educational Values in the Spiritual Development of the Mandar Community - Darwis, Darwis; Alhidayat, Wahyu; Arsalan, Muammar Zuhdi; Nuari, Fabry (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2025)
The values embedded in Sufi-oriented education play a vital role in cultivating spiritual awareness, which is increasingly relevant in addressing contemporary societal challenges. This study explores the efforts of K.H. Muhammad Tahir (Imam Lapeo) in instilling educational values grounded in Sufism within the Mandar community. Utilizing a qualitative descriptive method with a historical approach, data were gathered through interviews and document analysis. The findings indicate that Imam Lapeo, a respected Islamic preacher and educator, promoted core Sufi values patience (sabar), asceticism (zuhud), sincerity (ikhlas), and repentance (taubat). His roles as preacher, teacher, and moral exemplar were central to this process. These values were transmitted through contextualized and practical methods: sabr through daily religious and social practices; zuhd through a lifestyle of simplicity; ikhlas through sermons, personal instruction, and community service; and taubah through accessible and relatable religious discourse. Imam Lapeo’s integration of Sufi teachings with local contexts contributed significantly to the moral and spiritual development of the Mandar community.